Zeroes and poles of a characteristic function for Sturm–Liouville problem with nonlocal integral condition - Skučaitė, Agnė; Štikonas, Artūras (Lietuvos matematikos rinkinys, 2015)
This paper presents some new results on a spectrum for the Sturm–Liouville problem with one integral type nonlocal boundary condition depending on tree parameters (γ, ξ1, ξ2). Some new results on distribution of the sets of special points (poles, zeros and constant eigenvalue points) are presented. The research was partially supported by the Research Council of Lithuania (grant No. MIP-047/ 2014).